Economy and nature in the fourteenth century : money, market exchange, and the emergence of scientific thought - Kaye, Joel, 1946- (Cambridge studies in medieval life and thought, 1998)
This book provides perspectives on the ways in which scholastic natural philosophy anticipated and contributed to the emergence of scientific thought. Historians of medieval science have hesitated to step outside the sphere of intellectual culture in their search for factors influencing proto-scientific thought. This book searches for influences both within and beyond university culture, and argues that the transformation of the conceptual model of the natural world c.1260-1380 was strongly influenced by the contemporary rapid monetisation of European society. It analyses the impact of the monetised market place on the most characteristic concern of natural philosophy of the period: its preoccupation with measurement, gradation, and the quantification of qualities.